Force-velocity relationship in rowing and contribution to performance - Busseneau, P. F.; Delhaye, C.; Morel, B.; Simon, F.; Mornieux, G.; Bowen, M.; Samozino, P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Rowing performance depends on both capacities to produce high level of power output and to maintain it over time. The contribution of maximal capacities has been studied using force- or load-velocity relationships during squat and bench pull movements with good correlations between maximal power or force at low velocity with rowing performance (1,2). Yet interesting, these maximal capacity indexes have not been assessed during a rowing movement characterized by specific body configurations and coordination. Force-velocity (FV) relationship during rowing has just been explored once using a very specific ergometer (3), which has prevented from routine testing. The aims of this study were thus to test i) the feasibility to determine FV relationship during rowing using an usual rowing ergometer, and ii) the association between FV variables and rowing performance for different rower levels. METHODS: 59 rowers (from regional to Olympic rowers) performed 3 tests of 8 maximal strokes (with same range of motion) on a rowing ergometer (RowErg, Concept 2) instrumented with of force sensor between the handle and the chain and an incremental encoder on the outside nylock nut. The 3 tests were performed against 3 different resistances: i) maximum and ii) medium flywheel drag, and ii) minimum drag with flywheel covered by a plastic bag. Force, velocity, and power were averaged over each propulsion phase and then used to determine FV relationship from which were computed the theoretical maximal force (F0), velocity (V0), and power output (Pmax). Rowing performance was defined as the mean power over the last 2000m rowing test. RESULTS: FV relationships were well fitted by linear regression (median r²=0.981 [0.951-0.996]) with 10.6±2.4 experimental points covered 32.1±6.1% of the curve in the middle of the spectrum. F0, V0 and Pmax values were 1322±258, 3.50±0.33 and 1164±278, respectively. Mean power performance on 2000m rowing (362±90 W) test is strongly positively correlated to Pmax whatever the level (r = 0.61 to 0.90; p